Pemanfaatan Teknologi Informasi Dalam Pengembangan Pemasaran Ikan Asin Di Desa Umbul Tanjung Kecamatan Cinangka - Hartadi Wijaya (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2019)
The aim of the Community Service Program in Real-Learning Education and Community Empowerment (KKN-PPM) is to increase sales of the Umbul Tanjung village community, Cinangka District. The partners of this activity are the people of Umbul Tanjung Village, Cinangka District who have businesses or do not have their own businesses. Villagers who work as fishermen and locations to market their products are limited to the background of students to be able to help increase sales of their products including salted fish sales. The method of carrying out this service is through (1) Surveying through observation, interviews, and analysis of village considerations and potentials, (2) Training on account creation at the bukalapan or tokopedia sites. The results of this program add to people's knowledge and skills regarding (1) Utilization of Information Technology, and (2) selling salted fish in attractive packaging. This program is expected to facilitate the community in increasing their knowledge and skills in processing salted fish so that it is hygienic.